Pengaruh Pemberian Tepung Daun Kayambang (Salvinia molesta) terhadap Bobot Hidup, Persentase Lemak Abdominal dan Profil Lemak Darah Ayam Broiler - T. Setiawati; U. Atmomarsono; B. Dwiloka (Sains Peternakan: Jurnal Penelitian Ilmu Peternakan, 2014)
The study aimed to determine the effect of kayambang leaves flour (Salvinia molesta) as aconstituent of broiler ration that contain omega-3 fatty acids, on body weight, percentage of abdominal fat and blood lipid profile including High Density Lipoprotein (HDL) and Low Density Lipropotein (LDL). The material used was 100 broiler chickens unsexied 15 days old with an average a body weight of 500 ± 6.99g. Ration treatment consisted of T0 (ration without Salvinia molesta leaf meal); T1 (ration with Salvinia molesta leaf meal 6 % ); T2 (ration with Salvinia molesta leaf meal 12 %); and T3 (ration with Salvinia molesta leaf meal 18 % ). The results of the study showed Salvinia molesta leaf meal in the ration of broiler chickens affect (P< 0.05) body weight. Treatment T1,T2 and T3 showed decreases compared with the control diet (T0). Abdominal fat percentage showed no significant differences (P <0.05). Increase in LDL from control to treatment and decrease HDL were found in this experiment. The conclusion states that the provision of Salvinia molesta flour up to 18 % decreased the live weight of broiler, but did not decrease abdominal fat percentage. The LDL blood was increased and HDL was decreased due to addition of Salvinia molesta flour.Key words: Salvinia molesta, broiler chicken, fat, blood